2000
DOI: 10.1038/emm.2000.38
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome microdeletions in idiopathic azoospermia and non-mosaic type of Klinefelter syndrome

Abstract: The objective of this study was to elucidate the cause of the spermatogenic defect in idiopathic azoospermia and non-mosaic type of Klinefelter syndrome. Genomic DNAs from 9 cases of Korean idiopathic azoospermia and 6 of Korean non-mosaic type of Klinefelter syndrome were used for the detection of Y chromosome microdeletions by polymerase chain reaction using 60 primers. Microdeletions of the Y chromosome were found in 1 of 9 (11.1%) patients with idiopathic azoospermia, whereas none was deleted in non-mosaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
5
6
0
1
Order By: Relevance
“…In our study we found 12 (5%) cases with 47,XXY karyotype. Our results do not show microdeletion of Y chromosomes in patients with Klinefelter syndrome and are in accordance with the studies provided by Choe et al 28 , Tateno et al 29 , Lee et al 30 and Balkan et al 31 . De novo deletions of Yq are one of the most frequentlyoccurring chromosomal abnormalities in men and are believed to arise from recombination events between long stretches of highly repetitive DNA sequences during meiosis or early pre-implantation development 32 .…”
Section: Discussionsupporting
confidence: 93%
“…In our study we found 12 (5%) cases with 47,XXY karyotype. Our results do not show microdeletion of Y chromosomes in patients with Klinefelter syndrome and are in accordance with the studies provided by Choe et al 28 , Tateno et al 29 , Lee et al 30 and Balkan et al 31 . De novo deletions of Yq are one of the most frequentlyoccurring chromosomal abnormalities in men and are believed to arise from recombination events between long stretches of highly repetitive DNA sequences during meiosis or early pre-implantation development 32 .…”
Section: Discussionsupporting
confidence: 93%
“…This type of population effect was recently shown to affect genetic associations (Jin et al, 2003;Xue et al, 2006), indicating that Koreans appeared to be closely related to Manchurians, especially to the Harbin population and to Korean people living in the Changchun region where our data were collected. The genetic affinity or small genetic distance between these two population groups might explain the similar results obtained in this study with those of Lee et al (2000) and Choe et al (2007). Conversely, significant differences in results among studies are, in most cases, associated with the relatively large genetic distance between groups studied.…”
Section: Discussionsupporting
confidence: 68%
“…The fact that Northeast Chinese/Asian KFS patients generally lack AZF microdeletions, as was shown in this study, might suggest that the occurrence of these two defects most likely represents two separate independent genetic events that can occur in the same individual by chance. This observation has also been illustrated in other studies (Lee et al, 2000;Plaseski et al, 2008;Behulova et al, 2011;Rajpert-De et al, 2011). Furthermore, it was proposed that Y chromosome deletions do not facilitate non-disjunction events in paternal sex chromosomes, and do not cause a gain of X chromosomes (Rajpert-De et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A deficiência de androgênios leva também à redução da massa testicular e azoospermia, em consonância com o caso descrito (10). Na República da Coréia, o estudo de 9 pacientes com azoospermia revelou 6 (66,7%) novos portadores dessa síndrome (11). Além dessas alterações, percebem-se modificações na tonalidade da voz e no padrão masculino de distribuição de pêlos.…”
Section: Discussionunclassified